HIV incidence and sexual behavioral correlates among 4578 men who have sex with men (MSM) in Chengdu, China: a retrospective cohort study - Xinyi You; Stuart Gilmour; Wangnan Cao; Joseph Tak-fai Lau; Chun Hao; Jing Gu; Phuong Mai Le; Liping Peng; Dannuo Wei; Yang Deng; Xiaodong Wang; Huachun Zou; et al. (BMC, 2021)
Abstract Background The prevalence of HIV among men who have sex with men (MSM) in southwest China is still increasing. This study aimed to investigate the trend in HIV incidence and its associated risk factors among MSM in Chengdu, China. Method Incidence data were collected from the largest local non-governmental organization (NGO) serving MSM in Chengdu between 2012 and 2018, while information on sexual behaviors was collected from 2014. All MSM who received voluntary counseling and testing services (VCT) in the collaborating NGO at least twice during the study period were included. We calculated the HIV incidence density among MSM every 2 years and the overall incidence rate. A Cox proportional hazards regression model was employed to identify risk factors for HIV infection. Result A total of 4578 HIV-negative participants were included in the cohort. The total incidence density was 5.95 (95% CI: 5.37-6.56)/100 person-years (PYs) between 2012 and 2018. The segmented incidence density was 9.02 (95% CI: 7.46-10.78), 5.85 (95% CI: 4.86-6.97), 5.43 (95% CI: 4.53-6.46), and 3.09 (95% CI: 2.07-4.41)/100 PYs in 2012-2013, 2014-2015, 2016-2017, and 2018, respectively. After adjusting for sociodemographic characteristics, compared to participants without sexual partners within 6 months, MSM with one fixed partner (Adjusted Hazard Ratio, AHR = 1.18, 95% CI: 0.44-3.19) and more than five partners (AHR = 2.24, 95% CI: 0.81-6.20) had increased risk of HIV infection. MSM who used condom inconsistently had a higher risk of HIV infection (AHR = 1.87, 95% CI: 1.46-2.38) compared to consistent condom users. Conclusion The decreased HIV incidence density among MSM was potentially related to the successful comprehensive HIV prevention strategies in Chengdu. Multiple male sexual partnerships and inconsistent condom use during anal intercourse were risk factors associated with HIV occurrence.